CO2 Flow and its relation to biochemical properties in greenhouse horticultural crops - Albíter-Pineda, Juan Francisco; Vaca, Rocio; del Aguila, Pedro; Yánez-Ocampo, Gustavo; Lugo, Jorge (Ecosistemas y Recursos Agropecuarios, 2020)
In the conventional management of the soil for floricultural use, practices such as tillage, irrigation, the application of agrochemicals, among others, are used that favor yields, but also alter the physical, chemical and biological characteristics of the soil, which in turn are correlated with the CO2 given off by its microbial activity. Therefore, the objective was to determine the CO2 emission and relate it to the biochemical properties in greenhouse horticultural crops. The CO2 emitted was measured with the modified alkali trap technique, while the biochemical, physical and chemical properties were determined by traditional methods. The differences between the chemical variables (pH, electrical conductivity and organic matter) may be due to the management conditions, evidence was also observed that the management of each crop had an effect on the biological activity of the soil with changes in the emission of CO2 in the two times of sampling, the tomato crop being the one with the highest value. CO2 emissions peaked after irrigation due to moisture that increased soil microbial activity. There was little variation in N mineralization for both sampling times. Management was also related to changes in microbial biomass carbon and the qCO2 index, biochemical parameters were modified by the use of agrochemicals, moisture content and organic matter